Analisis Kepuasan Pelayanan Go-Food dengan Menggunakan PIECES Framework pada Mahasiswa/i STMIK BI - Arni Septiana Putri; Joy Nashar Utama Jaya; Hafes Aria Akbar (JURIKOM (Jurnal Riset Komputer), 2022)
In this modern era, transportation is one of the most important means of transportation in daily activities, especially in urban areas. This study focuses on analyzing the level of satisfaction of GoFood users or consumers, especially those who use GoFood services at STMIK BI Balikpapan. The results of the PIECES analysis are in the form of documents that become recommendations for improvements to be made to the system and then developed to improve the existing system. This study uses a quantitative descriptive method which aims to describe, summarize, various conditions, various situations and various variables that arise in the community which are the object of research based on the perceptions of respondents who use Go-food services to STMIK BI Balikpapan students. Based on the results of the calculation of the list of statements that have been distributed to respondents who are Go-food service users with a variable with an average value of 4.06 which is included in the satisfied category. The implementation of the information system currently used by STMIK BI Balikpapan students based on the PIECES framework has been going well. So the results of the calculation of the level of satisfaction of Go-food service users are at an average value of 4.06, where in the range of scores can be categorized as satisfied with Go-food service users as a medium for sharing information